Firefly-mimicking intensive and long-lasting chemiluminescence hydrogels - Yating Liu (Nature Portfolio, 2017)
Great efforts have been devoted to the development of chemiluminescence systems that emit light with high intensity over long periods of time. Here the authors show, firefly-mimicking intensive and long-lasting chemiluminescence hydrogels consisting of chitosan, N-(4-aminobutyl)-N-ethylisoluminol (ABEI) and catalyst Co2+.